Post-concussion Syndrome in Ukrainian Veterans: Physical and Mental Manifestations - Stebliuk, Vsevolod; Pronoza-Stebliuk, Kate (Journal of Education, Health and Sport, 2018)
In the structure of wounds on the Russian-Ukrainian war, traumatic brain injury takes 33 percent. And more than 80 percent is a mild TBI. Open clinical trial was provided by a multidisciplinary team in the National Military Medical Center (the Main military clinical hospital), Kyiv,Ukraine, under the leadership of the Military Medical Academy of Ukraine. 286 veterans, male, age 27,38±9,67 y.o with history of mTBI were observed for post-concussion syndrome. Causes of concussion were: isolated blast injury-69,3%, combine blast + shrapnel injury- 18,5% , car accidences - 6,1%, falls-7,1%/ Spectrum of PCS symptoms included all manifestations – as a physical , as mental heals problems, but dynamic in time of manifestations show the decreasing of physical signs and increasing of intensity of mental symptoms. Many patients with post-concussion syndrome also have symptoms of PTSD. In the studied group near the 40% of patients have PCL-m score more than 50. Our study shown that post-concussion syndrome, as a result of traumatic brain morphological and functional changes, powered with combat psycho trauma, lead to functional disorders: physical, emotional and cognitive.